L’écriture dans ses métamorphoses : potentialités et pertinence de l'artifice de langue - Michel Morel (Sillages Critiques)
Language witnesses the critical confrontation between the two sides of artifice: the negative, in the sense of mannerist repetition and the return of the same, the positive, in the sense of borderline inventiveness. The presentation defines five linguistic regimes related to five writers: John Lyly’s redundance, John Milton and the birth of poetic diction, Dylan Thomas’s canonical inventiveness, Gerald Manley Hopkins’s transgressive inventiveness and James Joyce’s neological cross-language overlap. It adumbrates a poetics of artifice in relation to the practices of Keats, Hopkins and Mallarmé, a poetics centred on the idea that linguistic exploration at its maximum and the hermeneutic extraction of the intrinsic significations can only meet and coincide in so far as language is inventive. The strength of artifice in writing is thus paradoxically to evidence and individualise the canonical dimension of language only when explores the borderline.